Knowledge, Attitude, and Practice of Infection Control Measures among Medical Students and Residents of a Private Medical College in Lahore, Pakistan: A Comparative Cross-sectional study: Knowledge, Attitude, and Practice of Infection Control Measures - Fatima, Rabail; Mazhar, Minahil; Mazhar, Ismail; Rai, Mir Muhammad; Cheema, Kanwal Hassan (Pakistan Journal of Health Sciences, 2025)
Healthcare workers, especially medical students, are constantly exposed to pathogens in hospitals, which significantly increases the risk of them being infected. Infection control measures are pivotal in safeguarding them from these infections and reducing any risk of transmissibility. Objective: To assess the knowledge, attitude, and practice of Infection Control Measures among medical students and residents of a private medical college in Lahore. Methods: This was a cross-sectional study conducted from April to June 2023 at CMH Lahore Medical College, using a purposive sampling technique that included residents and medical students from the third to the final year, regardless of age or other demographic factors. A pretested structured questionnaire was used. Data were analyzed using SPSS 23.0. Results: In this study, the total number of responses collected was 378. Out of these responses, 95% possessed good knowledge. 55.8% of participants showed a positive attitude towards infectious control measures. 91.5% of participants said that they followed good practices in infection control. On comparison between House officers, PGs, and undergraduates, significant p-values were obtained in terms of Knowledge, Practice, and Attitude, indicating that the participants in all three categories are well-informed regarding infection control measures and putting them into practice. Conclusions: This study highlighted the extent to which medical students and residents effectively implement infection control measures in their work environment. Furthermore, it underscores their level of receptiveness to these practices, shedding light on both strengths and areas for improvement.